Onset of autumn senescence in High Arctic plants shows similar patterns in natural and experimental snow depth gradients - Gehrmann, Friederike; Ziegler, Camille; Cooper, Elisabeth J. (Arctic Science, 2022)
Predicted changes in snow cover and temperature raise uncertainties about how the beginning and the end of the growing season will shift for Arctic plants. Snowmelt timing and temperature are known to affect the timing of bud burst, but their effects on autumn senescence are less clear. To address this, researchers have examined senescence under natural and experimental environmental gradients. However, these approaches address different aspects of plant responses and the extent to which they can be compared is poorly understood. In this study, we show that the effect of snowmelt timing on the timing of autumn senescence in High Arctic plants is the same between a natural and an experimental gradient in three out of four studied species. While the two approaches mostly produce comparable results, they give in combination greater insight into the phenological responses to predicted climate changes. We also showed that a short warming treatment in autumn delayed senescence by 3.5 days in Dryas octopetala L., which is a 10% extension of the growing season end for this species. Warming treatments have commonly been applied to the whole growing season, but here we show that even isolated autumn warming can be sufficient to affect plant senescence.